Bioecology and Beneficial Properties of Cashew Nuts - Ma’muraxon, Atabayeva (American Journal of Biology and Natural Sciences, 2024)
The morphology of cashew nuts and apples, their chemical composition, importance in production, bioecology and beneficial properties were analyzed.